Development and characterization of a CNS-penetrant benzhydryl hydroxamic acid class IIa histone deacetylase inhibitor. Issue 1 (1st January 2019) - Luckhurst, Christopher A.; Aziz, Omar; Beaumont, Vahri; Bürli, Roland W.; Breccia, Perla; Maillard, Michel C.; Haughan, Alan F.; Lamers, Marieke; Leonard, Phil; Matthews, Kim L.; Raphy, Gilles; Stott, Andrew J.; et al.
Graphical abstract: Highlights: Twenty hydroxamic acid inhibitors of class IIa histone deacetylases were synthesized. Inhibitor22 (CHDI-390576) was selective over class I and IIb histone deacetylases. Inhibitor22 can reach high exposure levels in mouse plasma, muscle and brain. Abstract: We have identified a potent, cell permeable and CNS penetrant class IIa histone deacetylase (HDAC) inhibitor22, with >500-fold selectivity over class I HDACs (1, 2, 3) and ∼150-fold selectivity over HDAC8 and the class IIb HDAC6 isoform. Dose escalation pharmacokinetic analysis demonstrated that upon oral administration, compound22 can reach exposure levels in mouse plasma, muscle and brain in excess of cellular class IIa HDAC IC50 levels for ∼8 h. Given the interest in aberrant class IIa HDAC function for a number of neurodegenerative, neuromuscular, cardiac and oncology indications, compound22 (also known as CHDI-390576) provides a selective and potent compound to query the role of class IIa HDAC biology, and the impact of class IIa catalytic site occupancy in vitro and in vivo .